IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE PARAGRAPH THROUGH SIMULTANEOUS ROUNDTBLE STRATEGY - Yudhi Pratama Tarigan and Yunita Agnes Sianipar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study attempts to improve students’ achievement in writing descriptive paragraphthrough simultaneous roundtable strategy. This study was conducted by using classroomaction research. The subject of the research was class VIII-5 SMP N 2 Berastagiconsisting of 30 students. The research was conducted in two cycles and consisted ofseven meetings. The instruments for collecting data were writing tests as thequantitative data and diary notes, observation sheet, and questionnaire sheet asqualitative data. Based on the writing score, students’ scores kept improving in everytest. In the first cycle test, the mean of writing score was 61,43. In the second cycle testthe mean of writing score was 75,13. Based on diary notes, observation sheet andquestionnaire sheet, it was found that students were actively involved in writingprocess. The result of the research showed that Simultaneous Roundtable Strategy canimprove students’ achievement in writing descriptive paragraph.